Angiopoietin‐2 Promotes Pathological Angiogenesis and Is a Therapeutic Target in Murine Nonalcoholic Fatty Liver Disease. Issue 3 (12th February 2019) - Lefere, Sander; Van de Velde, Frederique; Hoorens, Anne; Raevens, Sarah; Van Campenhout, Sanne; Vandierendonck, Astrid; Neyt, Sara; Vandeghinste, Bert; Vanhove, Christian; Debbaut, Charlotte; Verhelst, Xavier; Van Dorpe, Jo; et al.
Abstract : Angiogenesis contributes to the development of nonalcoholic steatohepatitis (NASH) and promotes inflammation, fibrosis, and progression to hepatocellular carcinoma (HCC). Angiopoietin‐2 (Ang‐2) is a key regulator of angiogenesis. We aimed to investigate the role of Ang‐2 and its potential as a therapeutic target in NASH using human samples, in vivo mouse models, and in vitro assays. Serum Ang‐2 levels were determined in 104 obese patients undergoing bariatric surgery and concomitant liver biopsy. The effect of the Ang‐2/Tie2 receptor inhibiting peptibody L1‐10 was evaluated in the methionine‐choline deficient (MCD) and streptozotocin‐western diet nonalcoholic fatty liver disease mouse models, and in vitro on endothelial cells and bone marrow–derived macrophages. The hepatic vasculature was visualized with µCT scans and scanning electron microscopy of vascular casts. Serum Ang‐2 levels were increased in patients with histological NASH compared with patients with simple steatosis and correlated with hepatic CD34 immunoreactivity as a marker of hepatic angiogenesis. Serum and hepatic Ang‐2 levels were similarly increased in mice with steatohepatitis. Both preventive and therapeutic L1‐10 treatment reduced hepatocyte ballooning and fibrosis in MCD diet‐fed mice and was associated with reduced hepatic angiogenesis and normalization of the vascular micro‐architecture. Liver‐isolated endothelial cells and monocytes from MCD‐fed L1‐10–treated mice showed reduced expression of leukocyte adhesion and inflammatory markers, respectively, compared with cells from untreated MCD diet‐fed mice. In the streptozotocin‐western diet model, therapeutic Ang‐2 inhibition was able to reverse NASH and attenuate HCC progression. In vitro, L1‐10 treatment mitigated increased cytokine production in lipopolysaccharide‐stimulated endothelial cells but not in macrophages. Conclusion: Our findings provide evidence for Ang‐2 inhibition as a therapeutic strategy to target pathological angiogenesis in NASH.